The Influence of Religiosity, Trust and Income on Muzakki's Interest in Paying Zakat to Institutions - Ikbal M Ikbal; Agus Rahman Alamsyah; Justita Dura (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2023)
Zakat is a form of material social worship, has a strategic and decisive position. However, there is a gap between the potential of zakat funds and the reality of collection due to the lack of public awareness.This study aims to empirically test the variables in the research that have been formulated in the formulation of the problem, namely whether there is an influence between religiosity, belief, and income on muzakki's interest paying zakat in BAZNAS Pangkalpinang city. The sample population used is 100 respondents. The data used in this study are primary data with validity test, reliability test, classical assumption test (normality, autocorrelation, and heteroscedasticity), F test, t test, and multiple regression analysis. Hypothesis testing was carried out with the help of the Statistical Package for the Sciences (SPSS) version 26 software. The result of this study is that religiosity partially does not affect the interest of muzakki in paying zakat, trust partially affect the interest of muzakki in paying zakat, income partially affect the interest of muzakki in paying zakat. Based on the results of the F (simultaneous) test, it shows that of the variable religiosity, belief, and income significance of the influence on the interest of muzakki to pay zakat. Thus the trust variable becomes the most dominant variable on the interest of muzakki in paying zakat at the Pangkalpinang City National Amil Zakat Agency. The implication of the research results is that zakat institutions conduct massive zakat religiosity literacy and improve the image of institutions to be more transparent, productive and contributive.